Phytoplankton abundance and Chlorophyll a concentration in four trophic regimes in the South Pacific Ocean - Cliff S Law (PANGAEA, 2025)
Samples were collected in the surface ocean of the South East Pacific Ocean in subtropical and sub-Antarctic water masses, above the Chatham Rise and at the entrance of the Cook Strait in well mixed water masses, creating distinct oligotrophic and eutrophic regimes, respectively. Regimes manifested in nutrient profiles, phytoplankton, and bacterial abundances, as well as in Chlorophyll a concentration, which are separated by size fractions.
In: Barthelmeß, Theresa; Cristi, Antonia; Deppeler, Stacy; Safi, Karl; Sellegri, Karine; Law, Cliff S; Engel, Anja (2025): Diel dissolved organic matter cycling and phytoplankton abundance in four trophic regimes of the South Pacific Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974276